2022
DOI: 10.3390/nano12040619
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Confinement of Chromonics: Effects of a Chiral Aminoacid

Abstract: Induced or spontaneous chirality in natural systems is an intriguing issue. In recent years, a lot of attention has been focused on chirality of chromonic liquid crystals, a class of materials that is able to self-assemble in columnar structures. However, the mechanism involved in the arising of chirality in these materials, that starts at the molecular level and controls the supramolecular structure, is poorly understood; however, it is certainly affected by ionic strength. In this work we present the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The production of well-defined size-dependent optical textures is the first crucial step toward the use of chromonic microspheres for practical applications. In particular, it has been recently demonstrated that the optical topology of microspheres degrades irreversibly over time due to temperature . Degradation can be slowed down by keeping the samples at 5 °C and can be avoided if samples are stored at −18 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of well-defined size-dependent optical textures is the first crucial step toward the use of chromonic microspheres for practical applications. In particular, it has been recently demonstrated that the optical topology of microspheres degrades irreversibly over time due to temperature . Degradation can be slowed down by keeping the samples at 5 °C and can be avoided if samples are stored at −18 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been recently demonstrated that the optical topology of microspheres degrades irreversibly over time due to temperature. 48 Degradation can be slowed down by keeping the samples at 5 °C and can be avoided if samples are stored at −18 °C. This paves the way for the fabrication of new biocompatible time–temperature indicators that can be used to monitor the cold food chain.…”
Section: Introductionmentioning
confidence: 99%